Diarylmethanes through an Unprecedented Palladium-Catalyzed C−C Cross-Coupling of 1-(Aryl)methoxy-1 H-Benzotriazoles with Arylboronic Acids - Singh, Manish K. (ChemCatChem, 2015)
1-(Aryl)methoxy-1H-benzotriazoles (ArCH(2)OBt) are bench-stable reagents that are prepared readily from 1H-benzotriazol-1-yl-4-methylbenzenesulfonate (BtOTs) and benzylic alcohols. These compounds, which contain a N–O–C bond, undergo cross-coupling with arylboronic acids by C–O bond scission with catalysts that comprise Pd(OAc)(2) and biarylphosphine ligands. Such reactivity of ArCH(2)OBt derivatives, leading to diarylmethanes, has not been described previously and constitutes a new activation of benzylic alcohols. With regard to the various ligands-metal complexes that support catalytic activity, it appears that those with smaller “percent buried volumes” (%V(bur)) provide better outcomes. This factor has been evaluated in the initial optimization studies and in further reactions with difficult coupling partners. Ligand electronics of the biaryl moiety seem to play a lesser role in this type of reaction. The bis-coordinating bis[(2-diphenylphosphino)phenyl]ether appears to be suitable to improve the yields of low-yielding reactions.